Efficacité de l’utilisation de l’application « le Tour de Culture » comme média littératie interculturelle Indonésienne-Française des lycéens de la SMA N 2 Ungaran - Haq Makarim, Bill; Handayani, Sri (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2025)
This study aims to determine students’ cross-cultural ability, the effectiveness of the “le Tour de Culture” application as a media for students’ cross-cultural literacy, and students’ response to utilizing the “le Tour de Culture” application as a media for cross-cultural literacy. This research is experimental research with one shot case study design, and the number of respondents was 36 students of SMA N 2 Ungaran. The methods used to collect data in this study were tests and. The results of this study indicate that the ability of SMA N 2 Ungaran students regarding cross-cultural knowledge of Indonesia-France is very good, with the percentage of students passing the Indonesian-French cross-cultural knowledge test of 94% with an average score obtained by students of 93.39. Then, 100% of SMA N 2 Ungaran students responded positively to the use of the “le Tour de Culture” application as a learning media for Indonesian-French cross-cultural literacy. On the other side, the percentage of class learning completeness is greater than the predetermined class completeness standard of 94.4%>85%. It can be concluded that the “le Tour de Culture” application is effective as a learning media for Indonesian-French cross-cultural literacy.